2009
DOI: 10.1158/0008-5472.can-08-2707
|View full text |Cite
|
Sign up to set email alerts
|

Design and Activity of a Murine and Humanized Anti-CEACAM6 Single-Chain Variable Fragment in the Treatment of Pancreatic Cancer

Abstract: Pancreatic ductal adenocarcinoma (PDA) is a lethal disease, with surgery being the only curative modality for localized disease, and gemcitabine with or without erlotinib remains the standard of therapy for unresectable or metastatic disease. CEACAM6 is overexpressed in human PDA independent of stage or grade and causes anoikis resistance when dysregulated. Because murine monoclonal antibody 13-1 possesses target-specific cytotoxicity in human PDA cell lines, we designed a humanized anti-CEACAM6 single-chain v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 29 publications
0
36
0
Order By: Relevance
“…For both adhesion molecules, antibody studies have revealed possible therapeutic potential in breast and pancreatic cancer 23 24 34 35…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For both adhesion molecules, antibody studies have revealed possible therapeutic potential in breast and pancreatic cancer 23 24 34 35…”
Section: Discussionmentioning
confidence: 99%
“…As previous studies suggested an important role for ALCAM localisation in tumour cells, cytoplasmic and membranous ALCAM staining was evaluated separately 16–22. As for both molecules, studies have revealed future therapeutic potential in cancer therapy, and a knowledge of ALCAM and CEACAM6 protein expression levels in distant metastasis is essential 23 24…”
Section: Introductionmentioning
confidence: 99%
“…4b). Furthermore, other reports that the anti-CEACAM6 single-chain variable fragment and maytansinoid (tubulin-interacting agent)-conjugated Ab against CEACAM6 led to inhibition of tumor growth might support the importance of preventing CEACAM6, rather than CEA, in the process of anoikis [34,35,36]. Moreover, C2-74 increased cell proliferation in some cases in this study, as shown in figure 3, suggesting that a human anti-CEA Ab does not help reverse the resistance of tumor cells in the metastatic phase.…”
Section: Discussionmentioning
confidence: 99%
“…It is overexpressed in pancreatic cancer cells by activating Ras mutations. CCN2 is thought to protect cells from hypoxia-induced apoptosis, providing a survival advantage for tumor cells under nonideal growth conditions and resulting in increased tumor growth [110]. CEACAM6 (CD66c) is an integral member of the carcinoembryonic antigen (CEA) family and is an important tumorassociated antigen overexpressed in human pancreatic cancer.…”
Section: Potential Targetsmentioning
confidence: 99%